The effectiveness of assertiveness communication training programs for healthcare professionals and students: A systematic review - Mieko Omura (2018)
© 2017 Elsevier Ltd Background Communication errors have a negative impact on patient safety. It is therefore essential that healthcare professionals have the skills and confidence to speak up assertively when patient safety is at risk. Although the facilitators to and barriers of assertive communication have been the subject of previous reviews, evidence regarding the effectiveness of interventions designed to enhance assertive communication is lacking. Thus, this paper reports the findings from a systematic review of the effectiveness of assertiveness communication training programs for healthcare professionals and students. Objective The objective of this review is to identify, appraise and synthesise the best available quantitative evidence in relation to the effectiveness of assertiveness communication training programs for healthcare professionals and students on levels of assertiveness, communication competence and impact on clinicians’ behaviours and patient safety. Data sources The databases included: CINAHL, Cochrane library, EMBASE, Informit health collection, MEDLINE, ProQuest nursing and allied health, PsycINFO, Scopus and Web of Science. The search for unpublished studies included: MedNar, ProQuest Dissertations & Theses A&I. Studies published in English from 2001 until 2016 inclusive were considered. Study eligibility criteria The review included original quantitative research that evaluated (a) any type of independent assertiveness communication training program; and (b) programs with assertiveness training included as a core component of team skills or communication training for healthcare professionals and students, regardless of healthcare setting and level of qualification of participants. Study appraisal and synthesis methods Studies selected based on eligibility criteria were assessed for methodological quality and the data were extracted by two independent researchers using the Joanna Briggs Institute critical appraisal and data extraction tools. Results Eleven papers were critically appraised using the Joanna Briggs Institute critical appraisal checklists. Eight papers from the USA, Australia, Ireland, and Taiwan were included in the review. Conclusions Interventions to improve assertive communication were reported to be effective to some degree with all targeted groups except experienced anaesthesiologists. Face-to-face and multimethod programs, support from leaders, teamwork skills training and communication techniques adapted from the aviation industry were identified as appropriate approaches for optimising the effectiveness of assertiveness communication training programs. Behavioural change as the result of assertiveness interventions was evaluated by observer-based rating scales during simulation, whilst self-perceived knowledge and attitudes were evaluated using validated scales. Future research should consider evaluation of sustained effect on behaviour change and patient safety.